"Real life" longevity of implantable cardioverter‐defibrillator devices. Issue 9 (22nd May 2017) - Manolis, Antonis S.; Maounis, Themistoklis; Koulouris, Spyridon; Vassilikos, Vassilios
Abstract : Background: Manufacturers of implantable cardioverter‐defibrillators (ICDs) promise a 5‐ to 9‐year projected longevity; however, real‐life data indicate otherwise. The aim of the present study was to assess ICD longevity among 685 consecutive patients over the last 20 years. Hypothesis: Real‐life longevity of ICDs may differ from that stated by the manufacturers. Methods: The study included 601 men and 84 women (mean age, 63.1 ± 13.3 years). The underlying disease was coronary (n = 396) or valvular (n = 15) disease, cardiomyopathy (n = 220), or electrical disease (n = 54). The mean ejection fraction was 35%. Devices were implanted for secondary (n = 562) or primary (n = 123) prevention. Single‐ (n = 292) or dual‐chamber (n = 269) or cardiac resynchronization therapy (CRT) devices (n = 124) were implanted in the abdomen (n = 17) or chest (n = 668). Results: Over 20 years, ICD pulse generator replacements were performed in 238 patients (209 men; age 63.7 ± 13.9 years; ejection fraction, 37.7% ± 14.0%) who had an ICD for secondary (n = 210) or primary (n = 28) prevention. The mean ICD longevity was 58.3 ± 18.7 months. In 20 (8.4%) patients, devices exhibited premature battery depletion within 36 months. Most (94%) patients had none, minor, or modest use of ICD therapy. Longevity was longest for single‐chamber devices and shortest for CRT devices. Latest‐generation devices replaced over the second decade lasted longer compared with devices replaced during the first decade. When analyzed by manufacturer, Medtronic devices appeared to have longer longevity by 13 to 18 months. Conclusions: ICDs continue to have limited longevity of 4.9 ± 1.6 years, and 8% demonstrate premature battery depletion by 3 years. CRT devices have the shortest longevity (mean, 3.8 years) by 13 to 17 months, compared with other ICD devices. These findings have important implications, particularly in view of the high expense involved with this type of electrical therapy.